Peran Pemerintah dalam Regulasi dan Pengawasan Kriptokurensi di Indonesia Sebagai Upaya Menjaga Stabilitas Ekonomi Digital - Steven Bredabu (Al-Wasathiyah: Journal of Islamic Studies, 2026)
The development of cryptocurrency as part of digital financial assets has brought significant changes to the economic system, including in Indonesia. The increase in the number of investors and the value of crypto transactions indicates its growing importance in the digital economy. However, the volatile and decentralized nature of cryptocurrencies poses challenges for the government in maintaining economic stability and protecting the public. This study aims to analyze the role of the government in the regulation and supervision of cryptocurrencies in Indonesia. The method used is a normative juridical approach by examining statutory regulations and the latest policies related to digital financial assets. The results show that the government has strengthened regulation through the transfer of crypto supervision to the Financial Services Authority (Otoritas Jasa Keuangan, OJK) since 2025, as well as the issuance of Financial Services Authority Regulation Number 23 of 2025. This policy marks the recognition of crypto as a digital financial asset within the national financial system and strengthens the integration of financial sector supervision in a more comprehensive manner. Nevertheless, challenges remain, such as regulatory gaps, the risk of money laundering, low public literacy, and the potential misuse of digital technology. Therefore, adaptive policies, effective supervision, and continuous public education are required to maintain the stability of the national digital economy amid the rapid development of financial technology.